Utilization of Industrial Wood Scraps in An Effort to Improve the Creative Industry of Calligraphy Art - Salman; Rahman, Maulana; Anda, Sabrian Tri; Putra, Rachmad Almi; Miswar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The creative industry is one of the important pillars of economic growth. Aceh Province is known as the Veranda of Mecca, as written in the book Bustanul Salatin. The creative industry in Aceh Province is currently still dominated by general products such as traditional crafts and is considered to not reflect Islamic identity in Aceh Province. Faisal Calligraphy Art Workshop is one of the businesses that operates in the field of calligraphy. To improve the quality and variety of calligraphy products, Efforts to Improve the Creative Industry are being carried out at the Faisal Calligraphy Art Workshop. This activity aims: (1) Enhancement insight and knowledge, (2) Increased creativity and product innovation, (3) Enhancement quantity and quality Product, (3) Increasing income. This activity was carried out at the Faisal Calligraphy Art Workshop business location which was attended by 10 training participants. Activities are carried out with Socialization, Focus Discussion Group (FGD), training and mentoring. The results of the service show that: (1) Increase partner insights through calligraphy derivative products originating from the use of wood waste, (2) increasing awareness of the importance of creativity in business actors, (3) increasing hard skill partners in processing industrial wood waste as raw material for making derivative products in the form of calligraphy art.